Psychopathology of Mother with ADHD Child in Jakarta's Primary School - Hapsari, Anggia; Widyawati, Ika; Hadisukanto, Gitayanti (ANIMA Indonesian Psychological Journal, 2011)
This study aims to obtain data of psychopathology proportion of mothers who have children with attention deficit/hyperactivity disorder (ADHD) and psychopathology features of mothers who have ADHD child. Subjects (mothers who have ADHD child and living together and function as primary caretakers) were randomly drawn proportionally from 30 elementary schools (from grade one to six) in DKI Jakarta from December 2010 until April 2011. Data were collected through MINI KID, Symptom Check List (SCL)-90, and subject demographic questionnaire. Results reveal that 60,4% of mothers with ADHD child have psychopathological symptoms with somatization (56,7%) as the most common symptom. The more a mother has psychopathological symptoms the worst is her perception towards her child. Through betterment of the mothers' psychopathology, her perception towards her child would be better, so that she could be more involved in the management/caring of her child. So a routine screening of mothers with ADHD child is most suggested. Penelitian ini bertujuan mendapatkan data proporsi psikopatologi ibu yang mempunyai anak dengan gangguan pemusatan perhatian dan hiperaktivitas (GPPH) dan gambaran psikopatologi ibu dengan anak dengan GPPH. Subjek penelitian adalah ibu kandung dari anak sekolah dasar di kelas satu sampai kelas enam yang tinggal bersama dan berfungsi sebagai pengasuh utama anak. Subjek diambil secara acak proporsional dari 30 SD di wilayah DKI Jakarta dari Desember 2010 sampai April 2011. Data diperoleh melelalui perangkat MINI KID, Symptom Check List (SCL)-90, dan kuesioner demografi. Hasil menunjukkan proporsi psikopatologi pada ibu dengan anak GPPH sebesar 60,4% (67 orang) dan gejala yang paling sering muncul adalah somatisasi (56,7%). Ibu yang semakin banyak memiliki gejala psikopatologi dapat memengaruhi persepsinya terhadap anaknya menjadi lebih buruk. Dengan perbaikan psikopatologi ibu maka persepsi terhadap anaknya menjadi lebih baik, sehingga bisa lebih banyak terlibat dalam tatalaksana anaknya. Dianjurkan untuk melakukan skrining rutin pada kaum ibu yang memiliki anak dengan ADHD.